Nerve growth factor deprivation results in the reactivation of latent herpes simplex virus in vitro. - Wilcox, C L (1987)
Primary sympathetic neuronal cultures were maintained for up to 5 weeks after inoculation with herpes simplex virus (HSV) without evidence of viral infection. Upon deprivation of nerve growth factor, the cultures produced infectious HSV, indicating that the cultures harbored latent HSV. This study demonstrates a function of nerve growth factor in the maintenance of HSV latency.